Mekanisme perbandingan income keuangan UMKM kerajinan songket di Kota Palembang sebelum dan setelah pandemi - Delpia Delpia; Kinaya Ananda Putri; Melisa Anggraini; Maya Panorama (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
Songket woven fabric is a superior product of the city of Palembang which needs to be preserved. The level of sales is increasingly taken into account by consumers both locally, regionally and even abroad. However, the popularity of songket has not been matched by the level of purchasing power of consumers who already know Palembang songket. The Covid-19 pandemic had a huge impact on the Indonesian economy so that the economic crisis occurred, including the songket woven craftsmen were also affected. They are haunted by uncertainty about the sale of songket woven fabrics. Their sales gradually decreased, thus affecting the decline in production and income. The focus of this research is to find out the mechanism for comparing the financial income of songket handicraft SMEs in Palembang City before and after the pandemic (Case Study at Songket Craft Shop Cek Ipah). This research uses a qualitative approach which is carried out by holding Forum Group Discussions (FGD), interviews or direct observations in the field, which can then be recorded through written notes or through a voice recorder. From the research results, it can be concluded that the Covid-19 pandemic had an impact on decreasing songket sales by around 70% at the Cek Ipah Songket Craft Shop.